A Digital Platform for Educational Robotics in Non-Formal Settings - Petenasi, Eduardo Paulino; Koga, Lucas Renato Hiroshi; Ribeiro, Carlos Eduardo; Trindade, Daniela De Freitas G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This study explores the development and implementation of a digital platform designed to deliver educational robotics to underprivileged and at-risk children within a non-formal educational context. The platform aims to democratize access to STEM education, fostering an inclusive environment where all students, regardless of their socioeconomic background, can develop critical skills for the 21st century. Aligned with the Brazilian National Common Core Curriculum (BNCC), the platform supports a variety of activities tailored to the competencies outlined in the BNCC, ensuring standardized and equitable educational outcomes. The initial testing phase, conducted by the project coordinators of an NGO's robotics program, involved an examination of the platform's functionalities and usability from the perspectives of educators, mediators, and students. The preliminary results indicate that, while the platform effectively supports educational objectives and provides valuable learning experiences, some adjustments are necessary to optimize its performance.